Neutrophilic dermatosis with necrobiotic changes as an unusual manifestation after the first shot of a COVID‐19 mRNA vaccine together with a high fever and liver injury - Shigeruko Iijima; Chiaki Enami; Mikio Sato; Takahiko Tsunoda; Kazunobu Otoyama (Frontiers Media S.A., 2023)
Abstract Coronavirus disease 19 (COVID‐19) mRNA vaccines sometimes cause various skin rashes. We report an unusual case of erythema nodosum‐like nodules with vesicular and pustular papules, which arose after the first shot of a COVID‐19 mRNA vaccine. A skin biopsy showed marked neutrophilic infiltration with necrobiotic changes throughout the dermis and subcutis. Immunohistochemically, CD8+ cells were much more common than CD4+ cells in the dense neutrophilic infiltrates. Many CD68+ macrophages were present around the CD8+ cells. No cases of neutrophilic dermatosis with necrobiotic changes have been reported. Thus, our findings should be added to the cutaneous adverse effects of the vaccines.